2018
DOI: 10.1002/anie.201802675
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Nitrogen Fixation at Boron

Abstract: No metal needed: Boron does the job! The activation of the inert dinitrogen molecule has fascinated chemists for ages. In a ground-breaking study Braunschweig and co-workers have now demonstrated that N activation can be achieved with the aid of the p-block element boron-a reactivity previously restricted to transition metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 30 publications
0
58
0
Order By: Relevance
“…In contrast with N‐doped carbon materials, B doping leads to the polarization of the BC σ‐bond and induces a positive charge on the boron atom owing to the lower electronegativity of boron (2.04) as compared to that of carbon (2.55). Moreover, since N 2 is a weak Lewis base, it is sufficient to generate a Lewis acid electrocatalytic site with an unoccupied orbital by boron doping to bind N 2 (Figure b) . Based on this rationale, a pure B 4 C compound was prepared that ultimately gave an impressive yield of ammonia and high Faradaic efficiency .…”
Section: Design Principles For Electrocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast with N‐doped carbon materials, B doping leads to the polarization of the BC σ‐bond and induces a positive charge on the boron atom owing to the lower electronegativity of boron (2.04) as compared to that of carbon (2.55). Moreover, since N 2 is a weak Lewis base, it is sufficient to generate a Lewis acid electrocatalytic site with an unoccupied orbital by boron doping to bind N 2 (Figure b) . Based on this rationale, a pure B 4 C compound was prepared that ultimately gave an impressive yield of ammonia and high Faradaic efficiency .…”
Section: Design Principles For Electrocatalystsmentioning
confidence: 99%
“…Moreover, since N 2 is a weak Lewis base, it is sufficient to generate a Lewis acid electrocatalytic site with an unoccupied orbital by boron doping to bind N 2 (Figure 4b). [42,75] Based on this rationale, a pure B 4 C compound was prepared that ultimately gave an impressive yield of ammonia and high Faradaic efficiency. [76] It is known that the acceptance (back donation) of electrons in boron-based carbon electrocatalysts contributes to the activation of inert NN triple bonds.…”
Section: Atom Regulation In Metal-free Materialsmentioning
confidence: 99%
“…In 2018, Hering-Junghans reported that hypovalent B species with the coexistence of lone-pair electrons and empty orbitals are similar to transition metals. [36] When doped into carbon materials, the B atoms could be positively charged and provided empty orbitals. Based on the Lewis theory that N 2 is a weak Lewis base, fabricating Lewis acid sites (empty orbitals of B) is considered to be a favorable strategy to realize the N 2 www.advancedsciencenews.com adsorption.…”
Section: Nonmetal Dopingmentioning
confidence: 99%
“…The most widely employed nonmetal‐atom dopant is boron (B) atom. In 2018, Hering‐Junghans reported that hypovalent B species with the coexistence of lone‐pair electrons and empty orbitals are similar to transition metals . When doped into carbon materials, the B atoms could be positively charged and provided empty orbitals.…”
Section: Defect Engineeringmentioning
confidence: 99%
“…1a), making many of them surprisingly stable under inert conditions. [1][2][3][4] Recently, transient dicoordinate (CAAC)-stabilised borylenes have drawn particular attention as compounds capable of activating and catenating N 2 , [21][22][23][24][25] the latter reaction being unprecedented even in transition metal chemistry.…”
Section: Introductionmentioning
confidence: 99%